The Power of Youth: Redefining India-Nepal Relations Through the Lens of a New Generation - Sharma, Jeetendr Kumar (International Journal of Social Sciences and Management, 2025)
Youth play a pivotal role in shaping India-Nepal relations, serving as catalysts for cultural diplomacy, policy advocacy, and addressing shared socio-economic and environmental challenges. Their contributions span digital engagement, grassroots activism, and innovation-driven initiatives, reflecting their potential to redefine bilateral ties. Despite facing structural barriers such as limited representation, digital inequities, and the impact of rising nationalistic sentiments, young people continue to bridge divides and foster collaboration. This study underscores the importance of youth-led initiatives in technology, climate action, and cultural exchanges while advocating for the strategic involvement of governments, NGOs, and educational institutions. Engaging youth effectively can pave the way for sustained peace, economic growth, and enriched cultural ties between India and Nepal. Int. J. Soc. Sc. Manage. Vol. 12, Issue-4: 191-200.